The shot: What the research has found - Ball, K. (coachesinfo.com)
There have been a number of research papers written examining the shot at goal in water polo (e.g. Davis and Blanksby, 1977; Whiting et al., 1985). These have described the movements which generate ball speed in elite throwers, compared high and low skilled players, males and females, fast and slow shooters to find important technical factors that make a good shooter. The major findings are summarized here. Content: - Introduction - Summary of Research Findings - Ball Speed - Shooting Technique - Technique Differences - Summary of Coaching Implications